Difficulties in recording mortality resulting from drug abuse - Marasović Šušnjara, Ivana; Definis Gojanović, Marija; Vodopija, Davor; Smoljanović, Ankica (Central European Journal of Public Health, 2014)
It is considered, according to statements from different sources, that data on the number of deaths in the population of a certain country or region are accurate and correct, but determining causes of death is, for different reasons, often incorrect. There is, therefore,a justified doubt that there are more inaccurately registered drug abuse-related deaths in state registries. Hence, this paper tends to show the most frequent difficulties encountered when recording mortality resulting from drug abuse.
Keywords: poruchy spojené s užíváním psychoaktivních látek; Cause of Death; Registries; Substance-Related Disorders; příčina smrti; Humans; lidé; registrace